Numerical simulation for in-cloud icing of three-dimensional wind turbine blades. (January 2018) - Wang, Zhengzhi; Zhu, Chunling
Icing will occur when wind turbines are installed in cold and humid regions. Blade icing will reduce the efficiency of wind turbines. In this paper, a numerical simulation method is proposed for glaze, mixed, and rime ice accretion on three-dimensional wind turbine blades. The air flow field is calculated by the multiple reference frame model and droplet trajectories are obtained using the Eulerian two-phase flow method. In the ice accretion calculation, a three-dimensional icing calculation model is established and a new water flow distribution method based on shear force and centrifugal force is presented. The calculation results of ice shapes are compared with the experimental results and the good agreement proves the validity of the icing numerical simulation method. Based on the calculation results, the influence of centrifugal force on the ice shape is studied. Finally, the droplet impingement characteristics and ice shapes of the wind turbine blade are simulated. The results show that the in-cloud icing of wind turbine blades occurs mainly near the leading edge. The icing thickness is thicker and the icing range is wider with the increase of spanwise length.